2007
DOI: 10.1359/jbmr.07s220
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Economy in Blacks

Abstract: ABSTRACT:The fact that fracture risk is lower and BMD is higher in blacks compared with whites is surprising in light of what is known about vitamin D status in blacks. Mean 25(OH)D levels are lower in blacks than whites at all stages of life, and a greater proportion of blacks meet criteria for vitamin D deficiency. The racial difference in serum 25(OH)D level is primarily caused by increased pigmentation reducing vitamin D production in the skin. In response to lower 25(OH)D levels and lower average calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…As expected, those variables acknowledged as risk factors for hypovitaminosis D in the general population, 61,64,66 have also been identified in HIVinfected patients. Weaker evidence was available for HIVrelated risk factors.…”
Section: Vitamin D Deficiencysupporting
confidence: 76%
See 1 more Smart Citation
“…As expected, those variables acknowledged as risk factors for hypovitaminosis D in the general population, 61,64,66 have also been identified in HIVinfected patients. Weaker evidence was available for HIVrelated risk factors.…”
Section: Vitamin D Deficiencysupporting
confidence: 76%
“…The three matched case-control analyses 27 a significantly higher prevalence in healthy controls in another, 30 and a significantly higher prevalence in HIV-infected patients in the third. 34 The study with the higher prevalence in the control group was performed in African-American subjects, 30 who are usually regarded as being at high risk of hypovitaminosis D. 61 As a result, both cases and controls had a very high rate of hypovitaminosis D. Paul et al 34 found a 20% greater prevalence of 25OHD ,20 ng/mL in HIV-infected patients, but they enrolled a very small sample (70 cases and 35 controls).…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…29 Skin colour is well recognised as a predictor of vitamin D status with numerous studies identifying lower levels in individuals with dark skin. [29][30][31] This is primarily due to increased melanin content reducing UVB absorption and subsequent vitamin D production. 32 It has also been reported that seasonal 40 This is supported by our study, which found that season was not an independent predictor and prevalence of deficiency and insufficiency were similar in the darkskinned group throughout the year, presumably because of persisting reduction in cutaneous production.…”
Section: Discussionmentioning
confidence: 99%
“…25 It has been widely recognised that mean 25(OH)D levels are lower in dark-skinned individuals at all ages, with greater risk of insufficiency and deficiency. [29][30][31] This racial difference is primarily due to increased melanin pigmentation which reduces UVB absorption and subsequent vitamin D production. 32 However, with recent public health campaigns emphasising the dangers of sunlight exposure and advocating intensive sun-block cream use, reports have also found high insufficiency rates, of around 60%, in the UK Caucasian population, and those with the fairest skin type to be, in fact, most deficient.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for pre-vitamin D 3 production is reduced further still by dark skin pigmentation. Other things being equal, the higher the eumelanin content, the lower the rate of previtamin D 3 production in the skin [2,20,21,[27][28][29][30][31][32][33][34][35][36][37][38]. When the zones of cutaneous pre-vitamin D 3 production potential are mapped following a previously established protocol [2], it is evident that lightly pigmented people inhabiting the zone near the equator can experience enough UVB through casual sun exposure on unprotected skin to produce physiologically adequate amounts of vitamin D. In the subtropical zone, there is at least one month during which there is insufficient UVB to catalyse pre-vitamin D 3 production for people with lightly pigmented skin, and during which they must rely on stored vitamin D (as 25-hydroxyvitamin D; 25(OH)D) to satisfy their physiological needs.…”
Section: Human Exposure To Ultraviolet Radiationmentioning
confidence: 99%